2021
DOI: 10.1155/2021/6611291
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Pancreas in the Gallbladder: Case Report and Literature Review

Abstract: Introduction. Heterotopic pancreas (HP) is the congenital presence of pancreatic tissue outside its normal location in the absence of vascular and anatomical connection with the main pancreas. HP can affect any part of the gastrointestinal tract, and it is mostly encountered in the stomach. The gallbladder is a rare site of HP, and our literature review revealed that only 38 cases were reported. We present a case of HP in the gallbladder that was presented with a picture of acute cholecystitis. After the case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Although, the male-to-female ratio of any type of EPT is 3:1, specifically for EPT in the gallbladder region, there is a female predominance, probably due to more cholecystectomies among women [ 8 , 9 ]. The median age of the reported cases was 46, with most patients being more than 40, contrary to our case, while chololithiasis coexisted with EPT in half of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, the male-to-female ratio of any type of EPT is 3:1, specifically for EPT in the gallbladder region, there is a female predominance, probably due to more cholecystectomies among women [ 8 , 9 ]. The median age of the reported cases was 46, with most patients being more than 40, contrary to our case, while chololithiasis coexisted with EPT in half of them.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the reported cases was 46, with most patients being more than 40, contrary to our case, while chololithiasis coexisted with EPT in half of them. Less than 40 cases of EPT in gallbladder have already been reported in the literature [ 9 ]. In almost all the cases, EPT in the gallbladder is diagnosed, after the resection and the histopathologic examination of the gallbladder.…”
Section: Discussionmentioning
confidence: 99%
“…The developing pancreases has areas of tissue that become separated from the main body of the pancreas [ 1 , 5 ]. In the literature <40 cases have been described [ 6 ]. Jean Schultz first described heterotropic pancreas in the 18th century, however, the first classification was made by Heinrich et al .…”
Section: Discussionmentioning
confidence: 99%
“…More rarely ectopic pancreas tissue can be found in other locations including the gallbladder and lungs [4]. In a systematic review published in 2021, Aborajooh et al reported a total of 38 cases from 1959 to 2020 of heterotopic pancreatic tissue in the gallbladder, representing approximately 1-2% of all cases of heterotopic pancreas [5]. Most cases were incidental diagnosis during cholecystectomies for symptomatic gallstone disease leading to an increased finding in women and an age above 40 [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review published in 2021, Aborajooh et al reported a total of 38 cases from 1959 to 2020 of heterotopic pancreatic tissue in the gallbladder, representing approximately 1-2% of all cases of heterotopic pancreas [5]. Most cases were incidental diagnosis during cholecystectomies for symptomatic gallstone disease leading to an increased finding in women and an age above 40 [4,5]. In approximately 10% of cases the tissue was thought to resemble gallbladder polyps or malignancy on imaging, often found as a submucosal lesion up to 3 cm with an endoluminal growth pattern, which formed the indication for surgery [2,5].…”
Section: Discussionmentioning
confidence: 99%